Effect of Ti addition on the thermal expansion anisotropy of Mo5Si3. (15th June 2017) - Azim, M.A.; Christ, H.-J.; Gorr, B.; Kowald, T.; Lenchuk, O.; Albe, K.; Heilmaier, M.
Abstract: (Mo, Ti)5 Si3 (T1) is a key component of novel Mo-Si-Ti composites which show superior creep resistance and a lower density than state-of-the-art Ni-based superalloys. However, pure Mo5 Si3 exhibits two shortcomings: (i) no oxidation resistance below 1650 °C and (ii) unusual high thermal expansion anisotropy (CTE(c)/CTE(a) = 2.2). The lack of oxidation resistance could be alleviated by Ti macroalloying. The aim of this study is to develop an in-depth understanding of varying Ti concentrations on the CTE in order to deduce appropriate Ti amounts in the T1 phase with low CTE mismatch and decent oxidation resistance. Therefore, experimental results, primarily obtained from high temperature X-ray diffraction refined by full pattern Rietveld analysis, were confirmed and elucidated by density-functional theory calculations. A clear 16k site preference is noted for Ti>12.5 at.%. The CTE anisotropy for Mo37.5Si30Ti(at.%) can be reduced to 1.34. Graphical abstract: Image 1